Multicentric Cutaneous Crohn's Disease: A Case Report and Review of Literature - Robert Prokopetz; J Barrie Ross; Peter Smith; Joseph J Sidorov (Canadian Journal of Gastroenterology)
A patient presented with skin lesions at sites not contiguous with Crohn's disease of the bowel and with specific histological features of Crohn's disease occurring two weeks from the onset of bowel symptoms. Currently a number of nonspecific skin conditions such as erythema nodosum, pyoderma gangrenosum and erythema multiforme are accepted as being the most common skin manifestations of Crohn's disease. It is likely, however, that specific lesions of Crohn's disease in the skin have been underdiagnosed either because of lack of biopsy or misinterpretation of the histology. Twenty-three cases with specific Crohn's disease in the skin have been recorded in the past 25 years, since the condition has been recognized. Sarcoidosis has been a common misdiagnosis. The literature relating to multicentric Crohn's disease is reviewed and attention drawn to its protean and masquerading features. An argument is made for the use of the term 'multicentric' rather than 'metastatic' in relation to cutaneous Crohn's disease.